2017
DOI: 10.1002/hec.3557
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of transient and persistent hospital efficiency: The case of Italy

Abstract: SummaryIn this paper, we extend the 4-random-component closed skew-normal stochastic frontier model by including exogenous determinants of hospital persistent (long-run) and transient (short-run) inefficiency, separated from unobserved heterogeneity. We apply this new model to a dataset composed by 133 Italian hospitals during the period 2008-2013. We show that average total inefficiency is about 23%, higher than previous estimates; hence, a model where the different types of inefficiency and hospital unobserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 84 publications
3
59
0
Order By: Relevance
“…In their study of 133 Italian hospitals, Colombi et.al. found that hospitals specialized in single treatments have higher transient inefficiency than general hospitals, indicating economies of scope [15]. In the same vein, a study in three States of the USA using stochastic frontier cost function presented some evidence that general hospitals are more efficient than specialized ones [34].…”
Section: Specialization Vs Economies Of Scopementioning
confidence: 96%
See 3 more Smart Citations
“…In their study of 133 Italian hospitals, Colombi et.al. found that hospitals specialized in single treatments have higher transient inefficiency than general hospitals, indicating economies of scope [15]. In the same vein, a study in three States of the USA using stochastic frontier cost function presented some evidence that general hospitals are more efficient than specialized ones [34].…”
Section: Specialization Vs Economies Of Scopementioning
confidence: 96%
“…The teaching status of a hospital often requires conducting additional clinical tests and diagnostics for the benefit of the residents this imply that teaching hospitals are likely to use higher level of resources than nonteaching hospitals for producing the same level of output [40]. An empirical study of the determinants of hospital efficiency in Italy using four-randomcomponent stochastic frontier model did not find statistically significant effect of teaching hospitals on transient (short-term) and permanent (long-term) inefficiency [15].…”
Section: Teaching Statusmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, each healthcare provider should only be benchmarked against their equilibrium level of inefficiency to obtain an unbiased measure of efficiency. To date, in the healthcare literature, only the study by Colombi et al [11] incorporated the persistent nature of inefficiency for 133 Italian hospitals. Nevertheless, this analysis excluded the concept of rigidities in altering inputs, and linked persistence to technical shortcomings and ineffective organisational structure.…”
mentioning
confidence: 99%